Kemampuan Komunikasi Interpersonal Guru Bimbingan Konseling dalam Menumbuhkan Self-Efficacy Siswa di Sekolah Menengah Pertama - Dewi Puspita Sari; Muhammad Ferdiansyah; Endang Surtiyoni; Arizona Arizona (Bulletin of Counseling and Psychotherapy, 2022)
The problems studied in this study are to describe and be able to determine the role of teachers' interpersonal communication skills in increasing students' self-efficacy. Because the counselor's efforts are needed to help overcome the problems they face by guiding them to more positive and harmonious behavior and can motivate them to learn. The method used in this study is a qualitative descriptive method using purposive sampling technique where this technique is to take research data sources with various considerations and is based on the existence of research objectives. From the results of research and data analysis shows that in communicating counseling guidance teachers are quite good in familiarizing themselves with students by way of approach. and provide strategies in the form of information services and individual counseling services. With a strategy in the form of information services and individual counseling services, interpersonal communication skills, counseling guidance teachers are able to make students confident in their abilities and more motivated than ever before.